1982
DOI: 10.1111/j.1432-1033.1982.tb06753.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cytochrome b/c1 Complex with Ubiquinol–Cytochrome c2 Oxidoreductase Activity from Rhodopseudomonas sphaeroides GA

Abstract: A cytochrome b/cl complex which catalyses the reduction of cytochrome c by ubiquinol has been isolated from Rhodopseudomonas sphaeroides GA. It contains two hemes b and substoichiometric amounts of ubiquinone-30 and of the Rieske Fe-S center per cytochrome c1, and is essentially free of reaction center and bacteriochlorophyll. The complex consists of three major polypeptides with apparent molecular masses of 40, 34 and 25 kDa. The 34-kDa polypeptide carries heme. Cytochrome c1 has a midpoint potential of 285 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(63 citation statements)
references
References 34 publications
6
57
0
Order By: Relevance
“…nmol cytochrome CT'. h-l, which is about 60% of that reported in [2]. These results indicated that the isolated cytochrome bc, complex is comparable to that of R. sphaeroides with respect to cytochrome composition and cytochrome c2 reduction activity.…”
Section: Resultssupporting
confidence: 74%
“…nmol cytochrome CT'. h-l, which is about 60% of that reported in [2]. These results indicated that the isolated cytochrome bc, complex is comparable to that of R. sphaeroides with respect to cytochrome composition and cytochrome c2 reduction activity.…”
Section: Resultssupporting
confidence: 74%
“…The absorbance maxima at 426 nm (c band), 530 nm (b band) and a split a band at 557 nm and 562 nm are characteristic for hemes of the b-type [26]. A similar splitting of the a band has been observed for other heme proteins, for example the cytochrome b L of the cytochrome bc 1 complex form Rhodopseudomonas sphaeroides GA [27]. Pyridine hemochrome reduced-oxidized difference spectra show maxima for the a and b band at 553 and 521 nm.…”
Section: Characterization Of the Heme Groups By Uv/visible And Epr Spmentioning
confidence: 57%
“…A procedure based on salt fractionation and sucrose density gradient centrifugation of octyl glucoside extracts was introduced by Hauska and coworkers for purification of the chloroplast b 6 f complex (45), and was adapted to isolation of the bc 1 complex from Rhodobacter (46) and the b 6 f complex of cyanobacteria (47). Clark & Hind (48) purified spinach b 6 f using a column of immobilized cytochrome c (horse).…”
Section: Purification Of Chloroplast and Cyanobacterial Bc 1 Complexesmentioning
confidence: 99%